2012
DOI: 10.1159/000338473
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Folate, Increased Vitamin B<sub>12</sub> and Homocysteine Concentrations in Women Delivering Preterm

Abstract: Background and Aim: Maternal nutrition is an important determinant of the duration of pregnancy and fetal growth, and thereby influences pregnancy outcome. Folic acid and vitamin B12 are involved in one-carbon metabolism and are reported to underlie intrauterine programming of adult diseases. Methods: In the present study, the levels of folate, vitamin B12 and homocysteine were measured in mothers delivering preterm (PT; gestation <37 weeks; n = 67), those delivering preterm due to preecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 86 publications
(53 reference statements)
2
39
2
Order By: Relevance
“…In contrast, a negative trend was seen in the control group. We have recently reported increased maternal plasma vitamin B 12 levels in women delivering preterm (Dhobale et al 2012a). Thus, a positive association between MMP3 and vitamin B 12 in the preterm group may be attributed to altered pathology in preterm pregnancy with the following possible mechanisms.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, a negative trend was seen in the control group. We have recently reported increased maternal plasma vitamin B 12 levels in women delivering preterm (Dhobale et al 2012a). Thus, a positive association between MMP3 and vitamin B 12 in the preterm group may be attributed to altered pathology in preterm pregnancy with the following possible mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…The associations between MMP/TIMP and vitamin B 12 levels were studied on a subset of term (nZ26) and preterm (nZ51) women from this study for which maternal plasma vitamin B 12 levels were estimated in our previous study (Dhobale et al 2012a). In this study, a positive association between placental MMP3 levels and maternal plasma vitamin B 12 levels was seen in the whole cohort (rZ0.265, PZ0.020, nZ77) and only in the preterm group (rZ0.277, PZ0.049, nZ51).…”
Section: Associations Of Placental Mmps and Timps With Maternal Plasmmentioning
confidence: 99%
“…In concordance with previous studies (Burgoon and others, 2002), we found that there was a significant increase in plasma homocysteine in pregnant mice administered a FD+SS diet throughout both the preconceptional and gestational period. The relationship between high homocysteine and poor pregnancy outcomes, independent of blood folate, has been established in both animal models and in human clinical populations (Bergen and others, 2012; Demir and others, 2012; Dhobale and others, 2012; Gadhok and others, 2011; Kim and others, 2012; van Mil and others, 2010). Administration of homocysteine to pregnant mice in the early stages of gestation has been demonstrated to cause fetal growth restriction, congenital abnormalities and increased fetal lethality (Han and others, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Norway found that higher serum holohaptocorrin concentrations in cord blood were correlated with increased gestational age at delivery (P = 0.026) (96). In contrast, a case-control study in India found that women with preterm delivery had significantly higher plasma vitamin B-12 concentrations at delivery than women with term deliveries (P = 0.003) (96,97).…”
Section: Literature Reviewmentioning
confidence: 97%